A First Look: Disparities in COVID-19 Mortality Among US-Born and Foreign-Born Minnesota Residents - Horner, Kimberly M. (Popul Res Policy Rev, 2021)
This research brief provides one of the first examinations of the impact of COVID-19 mortality on immigrant communities in the United States. In the absence of national data, we examine COVID-19 deaths in Minnesota, historically one of the major U.S. refugee destinations, using individual-level death certificates obtained from the Minnesota Department of Health Office of Vital Records. Minnesota’s foreign-born crude COVID-19 death rates were similar to rates for the US-born, but COVID-19 death rates adjusted for age and gender were twice as high among the foreign-born. Among foreign-born Latinos, in particular, COVID-19 mortality was concentrated in relatively younger, prime working age men. Moreover, the place-based and temporal patterns of COVID-19 mortality were quite distinct, with the majority of US-born mortality concentrated in long-term care facilities and late in 2020, and foreign-born mortality occurring outside of residential institutions and earlier in the pandemic. The disparate impacts of COVID-19 for foreign-born Minnesotans demonstrate the need for targeted public health planning and intervention in immigrant communities. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11113-021-09668-1.